Validity of test stimuli for nasalance measurement in speakers of Jordanian Arabic. (3rd July 2018) - Khwaileh, Fadwa A.; Alfwaress, Firas S. D.; Kummer, Ann W.; Alrawashdeh, Ma'moun
Abstract: Objective: The objective of the study was to establish the validity of passages for measuring nasalance of Jordanian speakers of Arabic. Design: Two Arabic text passages were constructed; the Spring Passage is devoid of nasal consonants and the Home Passage contains both oral and nasal consonants. Nasalance was measured for participants while reciting each passage three times. Perceptual ratings of hypernasality were also obtained for each participant on each passage using a 5-point equal-appearing rating scale. Participants: Forty-seven children and adults ranging in age between 9 and 26 years participated in the study. Twenty-three participants had no history of communication disorders, and 24 had repaired cleft palate. Results: Correlation coefficient between ratings of hypernasality and the nasalance scores was significant for the Spring Passage ( r = 0.88, p > 0.001) and for the Home Passage ( r = 0.78, p > .001). Using cutoff scores of 17% and 36% of nasalance for the Spring and the Home Passages, respectively, and a threshold score of 1.5 for hypernasality, sensitivity for the Spring Passage was 88% and the Home Passage was 78%. Conclusions: Results showed the validity of the Spring Passage and the Home Passage in measuring nasalance scores as proved by their high sensitivity and strong correlation with perceptual rating of hypernasality.